PENGARUH PELAKSANAAN PROGRAM MAGANG III TERHADAP KESIAPAN MENGAJAR MAHASISWA CALON GURU - Harti Oktarina (HISTOGRAM: Jurnal Pendidikan Matematika, 2021)
This study aims to determine the relationship between the implementation of the apprenticeship program III on the teaching readiness of student-teacher candidates for the Economic Education Study Program of STKIP Indonesian Development. This study uses a quantitative approach. The population in this study were students of the Economic Education Study Program of STKIP Indonesian Development. A sample of 158 respondents using a purposive random sampling technique. The data collection technique used was a questionnaire. Before the questionnaire is used, it has been tested first. The test results stated that the questionnaire was valid and reliable. Based on the results of the analysis test, it was found that the implementation of the apprenticeship program III had a positive and significant effect on the teaching readiness of prospective teachers in the Economic Education Study Program of STKIP Indonesian Development. This is indicated by the results of the t-test where the value of t count> t table (10.857> 1.976) and the significance value obtained is greater than the alpha value (0.000> 0.05). The result of the determination coefficient test obtained is 0.430, meaning that the variable implementation of the apprenticeship program III affects the teaching readiness of prospective teachers by 43% and the remaining 57% is influenced by other factors not present in this study.